História local no ensino de História: debate e representação no município de Porto Nacional/TO - Santos, Samara Silva dos (Universidade Federal do Tocantins, 2021)
This article aims to discuss and analyze the insertion of local history in history teaching in the municipality of Porto Nacional. The qualitative research uses as methodology the bibliographic theoretical studies produced on the theme, the dialogue with the legislation, and finally the application of a semi-structured questionnaire with a group of teachers who teach to students of the final years of elementary school (6th to 9th grade) in the state school system of the city. The objective of the proposed research aimed to verify how the teaching of local history is understood and worked by educators from the perspective of the particularities of a "small" space, understood in this work from the historical approach of the municipality in question. From the results, it can be considered that, although it is identified that local history teaching contributes to the student feeling part of the history, it is still poorly developed in the final years of elementary school, being sometimes understood as the history of the state.